A pro-inflammatory role for the Frizzled-8 receptor in chronic bronchitis. Issue 4 (21st January 2016) - Spanjer, Anita I R; Menzen, Mark H; Dijkstra, Akkelies E; van den Berge, Maarten; Boezen, H Marike; Nickle, David C; Sin, Don D; Bossé, Yohan; Brandsma, Corry-Anke; Timens, Wim; Postma, Dirkje S; Meurs, Herman; et al.
Abstract : Rationale: We have previously shown increased expression of the Frizzled-8 receptor of the Wingless/integrase-1 (WNT) signalling pathway in COPD. Here, we investigated if the Frizzled-8 receptor has a functional role in airway inflammation associated with chronic bronchitis. Methods: Acute cigarette-smoke-induced airway inflammation was studied in wild-type and Frizzled-8-deficient mice. Genetic association studies and lung expression quantitative trait loci (eQTL) analyses for Frizzled-8 were performed to evaluate polymorphisms in FZD8 and their relationship to tissue expression in chronic bronchitis. Primary human lung fibroblasts and primary human airway epithelial cells were used for in vitro studies. Results: Cigarette-smoke-exposure induced airway inflammation in wild-type mice, which was prevented in Frizzled-8-deficient mice, suggesting a crucial role for Frizzled-8 in airway inflammation. Furthermore, we found a significant genetic association (p=0.009) between single nucleotide polymorphism (SNP) rs663700 in the FZD8 region and chronic mucus hypersecretion, a characteristic of chronic bronchitis, in a large cohort of smoking individuals. We found SNP rs663700 to be a cis -eQTL regulating Frizzled-8 expression in lung tissue. Functional data link mesenchymal Frizzled-8 expression to inflammation as its expression in COPD-derived lung fibroblasts was regulated by pro-inflammatory cytokines in a genotype-dependent manner. Moreover, Frizzled-8 regulates inflammatory cytokine secretion from human lung fibroblasts, which in turn promoted MUC5AC expression by differentiated human airway epithelium. Conclusions: These findings indicate an important pro-inflammatory role for Frizzled-8 and suggest that its expression is related to chronic bronchitis. Furthermore, our findings indicate an unexpected role for fibroblasts in regulating airway inflammation in COPD.